2005
DOI: 10.1017/s0950268805004863
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antimicrobial resistance phenotypes in non-typhoidSalmonellaefrom human and poultry origins in France

Abstract: A total of 1873 strains from human origin and 4283 strains from non-human origin of Salmonella enterica serotypes Typhimurium, Enteritidis, Heidelberg, Hadar and Virchow, collected over three years 1993, 1997 and 2000, were examined in order to determine the rate of antimicrobial resistance to 12 antimicrobial drugs. The objective of the study was to describe and to compare the evolution of the main resistance types in human and non-human isolates, focusing on the poultry sector. The evolution and the rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
6
23
0
1
Order By: Relevance
“…Only Salmonella Stanley was resistant to tetracycline in a moderate rate (9.0%), all other antimicrobials tested were completely inhibiting by Salmonella Stanley. The same level of resistance of Salmonella Typhimurium to nalidixic acid (23%) was observed in a study performing in France [2]. Our results on the resistance of Salmonella Enteritidis to nalidixic acid were higher than what was seen in Europe in raw poultry (15.0%) [2].…”
Section: Discussionsupporting
confidence: 82%
“…Only Salmonella Stanley was resistant to tetracycline in a moderate rate (9.0%), all other antimicrobials tested were completely inhibiting by Salmonella Stanley. The same level of resistance of Salmonella Typhimurium to nalidixic acid (23%) was observed in a study performing in France [2]. Our results on the resistance of Salmonella Enteritidis to nalidixic acid were higher than what was seen in Europe in raw poultry (15.0%) [2].…”
Section: Discussionsupporting
confidence: 82%
“…We found a very high prevalence of antimicrobial resistance among the nontyphoid Salmonella isolates from outpatients in Henan Province compared to what has been reported in North America and Europe (2,5,10,12,19,22,23,27,29). In particular, we found that 54% of all isolates were resistant to ciprofloxacin and 23% were highly resistant.…”
Section: Discussionsupporting
confidence: 48%
“…In recent years, an increase in the occurrence of antimicrobial resistance, including resistance to quinolones, among salmonellae has been observed in many countries, particularly in Asia (2,10,19,22,23,27,29). The emergence of antimicrobial resistance is a matter of concern.…”
mentioning
confidence: 99%
“…In another result we found that 20% Salmonella was resistant to ciprofloxacin which is similar to the study conducted by Xia et al, 2009. Reports from other countries have found an increasing frequency of ciprofloxacin-resistant isolates (Cailhol et al, 2006;Davis et al, 1999). Ciprofloxacin-resistant isolates are involved with increased morbidity and mortality (Varma et al, 2005;Helms et al, 2004) and high frequency makes it difficult to use fluoroquinolones for treatment of Salmonella infections in humans.…”
Section: Resultssupporting
confidence: 85%